2021
DOI: 10.3168/jds.2020-19745
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stocking density and a blind on the behavior of Holstein dairy cows in group maternity pens. Part II: Labor length, lying behavior, and social behavior

Abstract: In natural settings, dairy cows separate from the herd to give birth. When kept indoors, seeking isolation before calving may be restricted and may depend on space and resources provided in maternity housing. The effect of group maternity pens on behavior around calving and labor progress is unknown. Therefore, the objective of this study was to determine the effects of stocking density and provision of a blind in group bedded pack maternity pens on lying and social behavior as well as length of labor of prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…This study was part of a larger study (Creutzinger et al, 2021b), and we had more animals than were needed for detailed behavioral analyses. The sample size analysis to determine the necessary number of ani-mals for detailed behavioral analysis can be found in Creutzinger et al (2021a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was part of a larger study (Creutzinger et al, 2021b), and we had more animals than were needed for detailed behavioral analyses. The sample size analysis to determine the necessary number of ani-mals for detailed behavioral analysis can be found in Creutzinger et al (2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our study design, it is unclear whether the increased distance between parturient animals and other cows in the pen was initiated by the focal animal or other cows. It may be less likely that other cows initiated the greater distance, as cows in late pregnancy are attracted to the scent of amniotic fluids (Jensen and Rørvang, 2018) and spend more time interacting with parturient cows as calving become more imminent (Creutzinger et al, 2021a). However, it is also unclear whether the focal cows initiated this change in distance from other cows, as the focal animals reduced their locomotor behavior in the few hours before calving.…”
Section: Separation Behaviormentioning
confidence: 99%
“…Maternity pens should be designed to ensure adequate space (>13 m 2 per cow), a soft and clean surface (deep straw bedding is preferred), easy access, proximity to prefresh area, and options for hiding (i.e., a plywood barrier covering half of the pen) [99,100]. A series of papers [30,32,101] demonstrated that providing the maternity pen with additional space and a physical blind (created using plastic road barriers and plywood, a steel gate, and shade cloth) may benefit periparturient cows and heifers, facilitating natural calving behaviors and reducing inflammation before calving.…”
Section: Management Strategies and Facilities To Optimize Animal Welfarementioning
confidence: 99%
“…When behavior was recorded in relation to signs of labor, Schuenemann et al (2011) found that multiparous animals laid down at the onset of abdominal contractions and remained recumbent until birth, whereas primiparous animals showed restless behavior characterized by increased lying bouts at the beginning of labor. Although the same authors ( Schuenemann et al, 2011 ) found no difference in the overall length of labor for primiparous and multiparous animals, other have found that primiparous animals have longer labors (e.g., 25 min longer for Creutzinger et al, 2021b and 21 min for Miedema et al, 2011 ).…”
mentioning
confidence: 86%
“…However, we also recommend that special care be given so that primiparous cows have the space needed to separate from other cows when they are expected to give birth. For example, producers are recommended to either move primiparous animals to individual calving pens in advance of calving or provide space and visual separation if kept in group calving pens (e.g., Creutzinger et al, 2021a , b ).…”
mentioning
confidence: 99%